Desigualdade intra grupos educacionais: teoria e evidência para o caso brasileiro - Costa, Ana Czeresnia (2006)
The objective of this analysis is to add a new perspective to the income inequality studies, introducing the within group inequality debate the inequality not explained by measurable characteristics of the worker or the job position. More specifically, this text aims on the part of inequality which cannot be explained by the educational differentials the within educational group inequality. Primarily, the within group inequality theory is presented. Based on texts poorly distributed in Brazil, it was indicated the existence of a kind of inequality that cannot be relinquished with educational investments. As following step, the recent Brazilian bibliography on inequality was analyzed, which highlights the center role played by years of study on income inequality reduction in Brazil and states that the combat of social inequality with educational expansion is the main equality policy the country should have. In this sense, little attention has been paid to the within educational groups inequality. Finally, based on the calculations of the within group inequality indexes with PNAD data (Brazilian Household Analysis), it was attempted to estimate its size and evolution in Brazil. The hypothesis of a relevant share of this kind of inequality in Brazil was corroborated, specially among high scholarship groups. The analysis indicates that the job position, the economy sector and the labor market experience are strong influences on the within educational group inequality as well. It was also found evidence pointing to a small influence of colour and/or gender discrimination. The main conclusions and evidences derived from this work show the relevance of the theme and that it can and should be kept as a field of study.